2015
DOI: 10.1002/adsc.201401013
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coupling of Arylacetonitriles and Primary Alcohols to α‐Alkylated Arylacetamides with Complete Atom Economy Catalyzed by a Rhodium Complex–Triphenylphosphine– Potassium Hydroxide System

Abstract: Ad irect synthesis of a-alkylated arylacetamides from arylacetonitriles andp rimary alcohols has been accomplished for the first time.I nt he presence of the rhodium complex [Rh(cod)Cl] 2 /triphenylphosphine/potassium hydroxide system,t he desired a-alkylated arylacetamides were obtained in 74-92% yield under microwave conditions.T he experimental results in this paper are in sharp contrast with previous reports, where the coupling of arylacetonitriles and primary alcoholsp roduced the a-alkylated arylacetonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 59 publications
1
64
1
2
Order By: Relevance
“…[58] Direct coupling of arylacetonitriles with primary alcohols by [{Rh(cod)Cl} 2 ]/PPh 3 /KOH was performed under microwave conditions,thus leading to a-alkylated arylacetamides in 74-92 %y ields. [59] Mechanistic studies revealed that arylacetonitriles are first a-alkylated with primary alcohols to produce a-alkylated arylacetonitriles,w hich are further hydrated with water, formed from the a-alkylation step,t o give the target products.Inthe case of using acetonitrile,both [{Ir(OH)(cod)} 2 ]/PPh 3 [60] and [RuHCl(PPh 3 ) 3 (CO)] [61] could effect its reaction with primary or secondary alcohols in the presence of ab ase [Eq. (13)].…”
Section: A-alkylation Of Nitrilesmentioning
confidence: 99%
“…[58] Direct coupling of arylacetonitriles with primary alcohols by [{Rh(cod)Cl} 2 ]/PPh 3 /KOH was performed under microwave conditions,thus leading to a-alkylated arylacetamides in 74-92 %y ields. [59] Mechanistic studies revealed that arylacetonitriles are first a-alkylated with primary alcohols to produce a-alkylated arylacetonitriles,w hich are further hydrated with water, formed from the a-alkylation step,t o give the target products.Inthe case of using acetonitrile,both [{Ir(OH)(cod)} 2 ]/PPh 3 [60] and [RuHCl(PPh 3 ) 3 (CO)] [61] could effect its reaction with primary or secondary alcohols in the presence of ab ase [Eq. (13)].…”
Section: A-alkylation Of Nitrilesmentioning
confidence: 99%
“…Nitriles are useful buildingb locks in organic synthesis. [8] With watera st he only by-product,t he alkylation of alkylnitriles with alcohols through hydrogen borrowing provides a" green" route for the synthesis of new nitrile compounds.T ransition-metal catalysts, including Ru, [3,9] Os, [10] Ir, [11] Rh, [12] and Pd, [13] have been employed for this reaction. The olefination of alkylnitriles with alcohols could afford a,b-unsaturated nitriles, which are also valuable intermediates in organic synthesis.…”
Section: In Memory Of Takao Ikariyamentioning
confidence: 99%
“…Since 1981, when Grigg and co‐workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, a lot of effort has been devoted to exploring various catalysts, including Ru, Rh, Ir, Pd, Os, Fe, and Mn. Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2‐(diphenylphosphino)‐ethyl)amine) pincer complex showed good activity for α ‐alkylated reaction of arylmethyl nitriles .…”
Section: Introductionmentioning
confidence: 99%